The effect of plasma treatment on shear bond strength of soft denture liner with two different types of denture base material (heat cure and light cure) - Abdullah, Zainab S; Mahmood, Wasmaa S; Ibrahem, Rafah A (Journal of Baghdad College of Dentistry, 2014)
Background: In this study we evaluate the effect of plasma treatment (oxygen and argon) gas in two different exposure times on the surface of heat cure and light cure acrylic resin.Materials and method: 100 specimens of heat cure and light cure acrylic resin were fabricated. The measurements of the samples were (75mm, 25mm and 4.5mm) length, width and depth respectively with stopper of 3mm depth. Two types of gas used oxygen and argon in (5,10) min by using (DC-glow discharge plasma device) then we apply cold cure soft lining material, with the help of Instron machine we test the shear stress value.Results: A highly significant effect after argon and oxygen gases treatment in both 5 and 10 min exposure times on shear bond strength to soft liner in heat cure denture base material. Conclusion: In this study we found that the exposure of heat cure acrylic resin to plasma gases (argon and oxygen) increase the shear bond strength (SBS) values significantly.